PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK PADA MATA PELAJARAN GEOGRAFI DI SMAN 2 BANDUNG - Zalmita, Novia; Yani, Ahmad (Jurnal Pendidikan Geografi Gea, 2015)
This research is motivated by the extent of globalization competition which requires students to have creative thinking skills in finding solutions of all life problems. To overcome those things, the efforts need to be made, hence, one of them is by using problem-based learning. Research was conducted in class X in SMAN Negeri 2 Bandung with 54 students participated in this research. Furthermore, this study used quantitative research with experimental approaches. The techniques for data collection was done by using the test (pretest and posttest), non-test (attitude scale with Likert category), and the teachers and learners observation sheet. Data analysis techniques were done with the help of SPSS for Windows version 20.0 to test data normality, data homogeneity and t-test. The findings showed that 1) before and after treatment was given, there were differences in the results of tests of creative thinking skills in the classroom using problem-based learning, 2) before and after treatment was given, this was revealed that there were differences in the results of tests of creative thinking skills in the class that did not use problem based learning, 3) there was no difference in the results of tests of creative thinking skills in the classroom use and are not using problem-based learning before treatment is given, 4) after treatment was given, this was found that there were differences in the results of tests of creative thinking skills between the class which used and which did not used problem-based learning.